PENGARUH LIKUIDITAS, PROFITABILITAS DAN TOTAL PERPUTARAN ASET TERHADAP HARGA SAHAM - Widyaningrum, Chintya; Suryono, Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is aimed to examine the influence of liquidity, pfofitability and total assets turnover to the share price through the annual financial statements which have been prepared by food and beverages companies which are listed in Indonesia Stock Exchange. The independent variables in this research are current ratio, return on assets and total assets turnover. Meanwhile the dependent variable is stock price.The populations in this research have been selected by using purposive sampling method to the food and beverages companies which are listed in Indonesian Stock Exchange (IDX) in 2011-2015 periods and based on the predetermined criteria then eight food and beverage companies have been selected as samples. The analystical method has been conducted by using multiple linear regression analysis and the SPSS (Statistical Product and Service Solutions) instrument. The result of the research shows that the F test of independent variables which consist of CR, ROA, and TATO give influence to the dependent variable which is stock price. One the t test CR gives significant and negative influence to the stock price with its regression coefficient is -389.118 and its significance level of 0.000. The ROA give positive and significant influence to stock price with its regression coefficient of 19671.985 and its significance level of 0.000. Meanwhile TATO does not give any influence to the stock price.Keywords : Liquidity, profitability, total assets turnover, stock price.